An Information System for Converting of ’Merdeka Belajar Kampus Merdeka’ Programs - Dian Ramadhani; Al Aminuddin; Yanti Andriyani; Evfi Mahdiyah; Riki Ario Nugroho (Journal of Information System Research (JOSH), 2023)
Merdeka Belajar Kampus Merdeka (MBKM) program enables universities to convert independently the programs into department courses hence those can be considered as its course credits. MBKM program guideline requires universities, specifically departments, to carefully convert MBKM program since they have to consider Program Learning Outcomes (PLO) and relevancy of courses in the conversion process. To follow the guideline, departments must explore learning outcomes of each courses and learning outcome of the programs. The job is certainly time and resource consuming. Therefore it needs to be supported by a reliable strategy and system to manage efficiently and effectively relational data between MBKM program, PLO and courses. Through these data, departments then enable to identify quickly related courses with those programs. This paper introduces a model to represent the conversion strategy. We then developed in-house application called e-OBE to implement the model to enable the departments to map PLO, MBKM program and course data efficiently and effectively. The mapping data can be used to retrieve department courses quickly in which their PLO are linked with MBKM program PLO. Finally, a recommendation based on text similarity from courses and MBKM program can be generated automatically to support department decision in the conversion process.